The Factors That Influence Self Acceptance in Adolescents with Divorced Parates: Literature Review - Tishi Nuradniy; Tience Debora Valentina (Universitas Negeri Surabaya, 2025)
Background: Indonesia faces various social issues, including the increasing number of divorce cases. Divorce not only affects the couple involved but also has a significant impact on their children, especially adolescents. During this stage, adolescents are expected to develop good self-acceptance to adapt and grow positively after their parents’ separation. Therefore, it is important to identify the factors influencing self-acceptance among adolescents with divorced parents. Objective: This study aims to identify factors affecting self-acceptance in adolescents whose parents are divorced. Method: This research employed a literature review with a narrative review approach. A total of 10 relevant articles published between 2013 and 2023 were selected from Google Scholar. Results: Findings show that self-acceptance in adolescents with divorced parents is influenced by internal factors (self-concept, positive thinking, religiosity, coping strategies, and realistic expectations) and external factors (social support, healthy relationships, and positive activities). Conclusion: Both internal and external factors contribute to the development of positive self-acceptance among adolescents with divorced parents. Abstrak Latar Belakang: Indonesia menghadapi berbagai permasalahan sosial, salah satunya adalah meningkatnya angka perceraian. Perceraian tidak hanya berdampak pada pasangan suami istri yang terlibat, tetapi juga memberikan pengaruh besar terhadap kehidupan anak-anak mereka, terutama pada masa remaja. Pada tahap ini, remaja diharapkan mampu mengembangkan penerimaan diri yang baik agar dapat beradaptasi dan berkembang secara positif setelah perceraian orang tuanya. Oleh karena itu, penting untuk mengidentifikasi faktor-faktor yang memengaruhi penerimaan diri pada remaja dengan orang tua yang bercerai. Tujuan: Penelitian ini bertujuan untuk mengetahui faktor-faktor yang memengaruhi penerimaan diri pada remaja dengan orang tua yang bercerai. Metode: Penelitian ini menggunakan metode tinjauan pustaka dengan pendekatan naratif terhadap 10 artikel yang diterbitkan pada tahun 2013–2023 dan diperoleh melalui Google Scholar. Hasil: Penelitian menunjukkan bahwa penerimaan diri pada remaja dengan orang tua bercerai dipengaruhi oleh faktor internal (konsep diri, pola pikir positif, religiusitas, strategi coping, dan harapan realistis) serta faktor eksternal (dukungan sosial, hubungan yang baik, dan kegiatan positif). Simpulan: Faktor internal dan eksternal berperan penting dalam membentuk penerimaan diri yang positif pada remaja dengan orang tua yang bercerai.